Discovery of non-covalent rhinovirus 3Cpro inhibitors by molecular docking, in vitro assays, molecular dynamics simulations and DFT analyses - Zhang, Susu; Zong, Keli; Ruan, Jiajun; Liu, Xiaojing; Zhao, Xu; Zhang, Youzhi; Hu, Chun; Li, Xingzhou (Frontiers in Pharmacology, 2025)
Human rhinovirus 14 (HRV-14) is a leading cause of the common cold, with its 3C protease (3Cpro) playing a crucial role in viral replication by cleaving polyproteins into functional proteins and enzymes. This makes 3Cpro a promising target for therapeutic intervention. In this study, to identify novel HRV-14 3Cpro non-covalent inhibitors, we performed a virtual screening of the TopScience and TargetMol (United States) database and selected 44 potential compounds for HRV-14 3Cpro inhibitory activity evaluation. Preliminary assays at 50 μM showed that compounds S21, S33, S34, and S43 exhibited inhibition rates of 80.51%, 96.5%, 75.59%, and 88.79%, respectively. Further characterization revealed that S21 and S34 exhibited moderate activity with IC50 values of 30.40 ± 0.67 μM and 24.11 ± 0.55 μM, respectively, while S33 and S43 displayed stronger inhibition with IC50 values of 11.32 ± 0.71 μM and 2.33 ± 0.5 μM, respectively. To elucidate the binding mode of S33 and S43 to HRV-14 3Cpro, we conducted all-atom molecular dynamics (MD) simulations and density functional theory (DFT) calculations on the docked complexes of compounds S33 and S43 with HRV-14 3Cpro. MD analyses, including principal component analysis (PCA), free energy landscapes (FEL), and dynamic cross-correlation matrices (DCCM), revealed that both compounds enhanced the structural stability of the HRV-14 3Cpro while reducing its flexibility and internal dynamics. These findings suggested that S33 and S43 are promising candidates for optimization and clinical development as novel non-covalent HRV-14 3Cpro inhibitors.